Risk Factors of Infected CAPD in the First Three Months of ESRD on CAPD Patients - Intarawongchot, Pisith (Journal of Health Science of Thailand, 2017)
Infected CAPD is the more common complication of the treatment. Serum albumin level, Hb level, female gender, smoking,old age, obesity, DM, technique of cycle exchange, duration of treatment, hypokalemia were known as significant risk factors. Yet, infeceted condition in the first 3 months were basically excluded in most studies. To analyze peritonitis rate in the first 3 months, a prospective study in CAPD patients who attended at our facility was carried out from November 1, 2008 to November 1, 2011. In all, 189 CAPD patients were included in this study. There were 26 infected CAPD patients and 163 non- infected CAPD patients. A comparative analysis between the infected CAPD group and the non-infected CAPD groups was done. Each factor that might be a risk factor was tested by Pearson chi-square test. Each significant factor were together tested by multiple logistic regression, 95% confidence and odds ratio. There were 13.8 percent of 189 total CAPD patients developed catheter association infected CAPD. Under multiple logistic regression analysis, traumatic Tenckhoff catheter history,poor environment and non training caregivers or self learning care givers increased infection rate 20.58, 8.38, 5.46 times more than that of the noninfected CAPD group. It is,therefore recommended that avoidance of trauma due to Tenckhoff catheter, non trainning care givers or selftraining care givers, and appropriation environment should be success keys to decrease infected CAPD rate in the first three months.